1970
DOI: 10.1007/bf01398248
|View full text |Cite
|
Sign up to set email alerts
|

Direkte Beobachtung einzelner magnetischer Flußquanten in supraleitenden Hohlzylindern. III

Abstract: Direct Observation of Single Magnetic Flux-Quanta in Superconducting Tubes. III By use of electron interferometry the trapped magnetic flux was investigated in superconducting microcylinders (inner diameter < 1 gm). Even in thin walled cylinders (wall thickness < penetration depth) at temperatures near the superconducting transition the flux was found to be quantized in integer multiples hc/2e.In the appendix an interpretation of the magnetic Aharonov-Bohm effect as a local interaction between the excluded fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1974
1974
2008
2008

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Most of the relevant properties of the quantum effects of fluxes can be discussed in terms of the two-slit interference experiment with electrons. Evidence for the AB effect have been found by Lischke [4] and Tonomura et al [5] in such experiments.…”
Section: Introductionmentioning
confidence: 66%
“…Most of the relevant properties of the quantum effects of fluxes can be discussed in terms of the two-slit interference experiment with electrons. Evidence for the AB effect have been found by Lischke [4] and Tonomura et al [5] in such experiments.…”
Section: Introductionmentioning
confidence: 66%
“…These shielding electrons could in principle bring an additional phase contribution to the conventional AB phase shift of the incident electrons. Experiments carried out by Lischke, [2] Möllenstedt et al [3] and Tonomura et al [4] have demonstrated however the persistence of the conventional AB shift in the presence of metallic shields.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental observations 1 ),2) reveal that there exists some discrepancy between the total trapped magnetic flux f/)!n existing in a multiply connected superconductor and total flux f/)ex observed outside the superconductor. Lischke 1 ) measured the temperature dependence of the total flux trapped in a superconductor cylinder with use of Aharanov-Bohm effect,3) The superconductor cylinder is with inside radius p and thickness d as seen in the insert of Fig_ 1.…”
mentioning
confidence: 99%
“…The observed temperature dependence of f/)ex is shown in Fig_ 1 by solid line. When p'2>d and J..>d, a calculation 4 ) shows that the total trapped flux f/)in existing in the cylinder is , , , (1) where J.. is the penetration depth of the superconductor, f/)o=h/2e is the flux quantum, and C' is taken inside the superconductor. With the increase of temperature T to the transition temperature Te, the penetration depth J.. increases monotonically and diverges at T = Te.…”
mentioning
confidence: 99%